The Influence of Self-Confidence on English Language Learning: a Systematic Review - Zanyar Nathir Ghafar (International Journal of Applied Educational Research (IJAER), 2023)
English communication skills are necessary for academic and professional success worldwide. A major factor in English language proficiency is self-confidence. This literature review consolidates research on self-confidence and English language proficiency and identifies effective ways to boost language learners' self-confidence. The study shows that those with high self-confidence in their English language skills are more likely to learn a second language and speak it well. Self-confidence boosts drive, tenacity, and language acquisition challenge-taking. The findings found that self-confident people have better pronunciation, vocabulary, and grammar, which are essential for English communication. Self-confidence and English language proficiency is complex and affected by individual traits, cultural history, and language acquisition experiences. Effective treatments to improve language learning confidence are needed for optimal results. Language teachers and educators can use setting goals, encouraging, and reflecting on one to boost students' self-confidence and English language ability in academic and professional settings.